Imunska toleranca - Jeras, Matjaž (Zdravniški vestnik, 2011)
Background: Regulation of human immune system through mechanisms of immune tolerance is an exceptionally important part of the homeostasis that protects the integrity of our organism. Whenever we talk about immune responses, we primarily consider them as an efficient activation of numerous factors enabling our cellular and humoral immunity to protect us against nocive effects of various forms of pathogens. However, each of these activation processes must be adequately regulated by appropriate immunosuppressive mechanisms, thereby providing a rational extent of immune reactivity without exhausting the organism and at the same time assuring a rather quick reestablishment of normal physiological conditions, which is a basic task of immune homeostasis. Such natural and dynamic yin/yang balance, being crucialfor the wellbeing of each individual, can only be provided by well orchestrated specific interactions between activated effector immune cells, such as Th1, Th2 and Th17 CD4+ lymphocytes, CD8+ cytotoxic T lymphocytes, natural killer cells (NK) and other activating factors on one side, and the oppositely functioning immunoregulatory effectors, such as regulatory CD4+ andCD8+ T lymphocytes, tolerogenic antigen-presenting cells (APC) and other immunosuppressive factors, on the other. In the case of a colapse or an imbalance of this system, there are serious consequences that are reflected inthe occurrence of autoimmune diseases, in which case the immune system is unsuccessfully suppressing the reactivity against self-antigens or the outburst of cancer cells, due to the excessive negative regulatory immune mechanisms that are actively protecting tumors. Conclusions: In this review weare presenting novel findings regarding the mechanisms of tolerance as an important part of immune homeostasis and discussing the potential of translating this knowledge into clinical setting by developing advanced cell therapies, mostly for treating autoimmune diseases and preventing graft rejection following allogeneic tissue and organ transplantation.
Keywords: imunologija; imunska toleranca; imunski sistem